An investigation into the plight of orphans and vulnerable children in two high schools in the Libode district in the former Transkei - Osei-Agyakwa, Cecilia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.